Assessing the risk of hepatocellular carcinoma by combining liver stiffness and the controlled attenuation parameter. Issue 10 (10th July 2019) - Izumi, Takaaki; Sho, Takuya; Morikawa, Kenichi; Shigesawa, Taku; Suzuki, Kazuharu; Nakamura, Akihisa; Ohara, Masatsugu; Kawagishi, Naoki; Umemura, Machiko; Shimazaki, Tomoe; Kimura, Megumi; Nakai, Masato; et al.
Abstract : Aim: Ultrasound technology can now be used for liver stiffness measurement (LSM) and for evaluating the amount of hepatic fat quantitatively known as the controlled attenuation parameter (CAP). This study aimed to determine the applicable cut‐off values of LSM and the CAP for primary hepatocellular carcinoma (HCC), and to investigate their clinical usefulness for assessing HCC risk in patients with chronic liver disease. Methods: A total of 1054 patients (88 with primary HCC and 966 without HCC) whose LSM and the CAP were measured by transient elastography with clinically evident hepatitis C virus (419 patients), hepatitis B virus (377 patients), and non‐alcoholic fatty liver disease (258 patients) were enrolled in this study. Subsequently, a total of 966 patients who did not have HCC initially were followed, and the usefulness of the cut‐off values of LSM and CAP for HCC development were evaluated. Results: In hepatitis C virus patients, the incidence of HCC development was significantly higher among those with a combination of LSM ≥8.0 kPa and CAP ≤221 dB/m than among those with other values (log–rank test 0.0239, hazard ratio 2.66, 95%CI 1.07–6.47, P = 0.0362). In non‐alcoholic fatty liver disease patients, the incidence of HCC development was significantly higher among those with a combination of LSM ≥5.4 kPa and CAP ≤265 dB/m than among others (log–rank test 0.0040, hazard ratio 8.91, 95% CI 1.47–67.97, P = 0.0192). Conclusion: In the hepatitis C virus and non‐alcoholic fatty liver disease groups, a combination of LSM and the CAP cut‐off values would be useful for screening to identify the high‐risk group for primary HCC development.